The Real Economy Essays in Ethnographic Theory - Neiburg, Federico; Guyer, Jane I. (HAU Books, 2020)
This collection highlights a key metaphor in contemporary discourse about economy and society. The contributors explore how references to reality and the real economy are linked both to the utopias of collective well-being, supported by real monies and good economies, and the dystopias of financial bubbles and busts, in which people's own lives "crash" along with the reality of their economies. An ambitious anthropology of economy, this volume questions how assemblages of vernacular and scientific realizations and enactments of the economy are linked to ideas of truth and moral value; how these multiple and shifting realities become present and entangle with historically and socially situated lives; and how the formal realizations of the concept of the "real" in the governance of economies engage with the experiential lives of ordinary people.